Contextualizing yellow light-emitting electrochemical cells based on a blue-emitting imidazo-pyridine emitter - Fresta, Elisa; Volpi, Giorgio; Garino, Claudio; Barolo, Claudia; Costa, Rubén D. (Polyhedron, 2018)
This work provides the synthesis, structural characterization, electrochemical and photophysical features, as well as the application in light-emitting electrochemical cells (LECs) of a novel small molecule belonging to the pyridilimidazo[1,5-a]pyridine family, namely 3-(2-methoxyphenyl)-5-methyl-1-(6-methylpyridin-2-yl)H-imidazo[1,5-a]pyridine (Me-impy). This compound shows a low-cost and facile synthesis, excellent redox properties, and a high photoluminescence quantum yield (Φ) of 0.4 associated to a blue emission (∼436 nm) in solution. Despite these appealing features, the emission in solid state is red-shifted to the yellow region, owing to its prone aggregation character. Additionally, the electroluminescence response shows a broader and red-shifted emission even upon dilution of Me-impy thin films with polymethyl methacrylate (PMMA). Herein, we report an in-depth study on the aggregation features and its impact on the electroluminescence response of Me-impy, providing relevant information to design small-molecule based LECs. [Display omitted] This work provides the synthesis, structural characterization, electrochemical and photophysical features, as well as the application in light-emitting electrochemical cells (LECs) of a novel small molecule belonging to the pyridilimidazo[1,5-a]pyridine family, namely 3-(2-methoxyphenyl)-5-methyl-1-(6-methylpyridin-2-yl)H-imidazo[1,5-a]pyridine (Me-impy). This compound shows a low-cost and facile synthesis, excellent redox properties, and a high photoluminescence quantum yield (Φ) of 0.4 associated to a blue emission (∼436 nm) in solution. Despite these appealing features, the emission in solid state is red-shifted to the yellow region, owing to its aggregation character. Additionally, the electroluminescence response shows a broader and red-shifted emission even upon dilution of Me-impy thin films with polymethyl methacrylate (PMMA). Herein, we report an in-depth study on the aggregation features and their impact on the electroluminescence response of Me-impy, providing relevant information to design small-molecule based LECs.